Analisis Perbandingan Kinerja TCP Vegas dan TCP New Reno Menggunakan Antrian Drop Tail - Dony Fahrudy; Bambang Sugiantoro (JISKA (Jurnal Informatika Sunan Kalijaga), 2022)
TCP was developed to deal with problems that often occur in the network, such as congestion problems. Congestion can occur when the number of packets transmitted in the network approaches the network capacity which can cause network problems. This can be overcome by implementing TCP and queue management. In this research, we will test the performance of TCP Newreno and TCP Vegas using NS-2 in the Drop Tail queue. The performance parameters used are throughput, packet drop, and congestion window with additional buffer capacity. The test results for the congestion window and packet drop parameters, TCP Vegas has better performance when the buffer gets bigger when congestion occurs with the congestion window smaller than TCP New Reno and the average packet drop is 18.33 packets compared to TCP New Reno with an average of 18.33 packets. average 41.67 packets. For throughput parameters, TCP New Reno has better performance with an average of 6.77253 Mbps than TCP Vegas with an average of 4.29693 Mbps. From testing and analysis that TCP Vegas has better performance than TCP New Reno when using Drop Tail queues.